Ubiquitin Interacting Motifs: Duality Between Structured and Disordered Motifs - Lambrughi, Matteo; Maiani, Emiliano; Aykac Fas, Burcu; Shaw, Gary S.; Kragelund, Birthe B.; Lindorff-Larsen, Kresten; Teilum, Kaare; Invernizzi, Gaetano; Papaleo, Elena (Frontiers in Molecular Biosciences, 2021)
Ubiquitin is a small protein at the heart of many cellular processes, and several different protein domains are known to recognize and bind ubiquitin. A common motif for interaction with ubiquitin is the Ubiquitin Interacting Motif (UIM), characterized by a conserved sequence signature and often found in multi-domain proteins. Multi-domain proteins with intrinsically disordered regions mediate interactions with multiple partners, orchestrating diverse pathways. Short linear motifs for binding are often embedded in these disordered regions and play crucial roles in modulating protein function. In this work, we investigated the structural propensities of UIMs using molecular dynamics simulations and NMR chemical shifts. Despite the structural portrait depicted by X-crystallography of stable helical structures, we show that UIMs feature for both helical or intrinsically disordered motifs. Our results shed light on a new class of disordered UIMs. This group is here exemplified by the C-terminal domain of one isoform of ataxin-3 and a group of USP-containing proteins. Intriguingly, UIMs not only bind ubiquitin. They can be a recruitment point for other interactors, such as parkin and heat shock protein Hsc70-4. Disordered UIMs can provide versatility and new functions to the client proteins, opening new venues for research on their interactome.